The Effect of PhET Simulation-Based Learning on The Ability to Understand Elementary Science Concepts in Work and Energy Material - Bahtiar, Bahtiar; Ibrahim, Ibrahim; Maimun, Maimun (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2024)
This research aims to determine the effect of using PhET Simulation on understanding Natural Science concepts in prospective teachers, with a focus on the material "Work and Energy." This research is quantitative research with a quasi-experimental method. This research involved two groups of prospective elementary school teachers, where one group used PhET Simulation-based learning while the other group used conventional learning methods. Data on understanding science concepts was collected through pretest and posttest, and analyzed using statistical tests. The results showed that there was a significant increase in understanding of science concepts in both groups, but a greater increase occurred in the group that used PhET Simulation. The implications of this research emphasize the importance of integrating interactive technology in science learning to increase understanding and involvement of prospective teachers.